Pengaruh Penggunaan Sistem ERP, Ketersediaan Data dan Ketersediaan Laporan terhadap Pengambilan Keputusan pada Perkebunan Kelapa Sawit: Studi Kasus PT Ciliandra Perkasa - Kurniawan, Roni (Bina Nusantara University, 2012)
Every decision made by top management determines the company objection. One tool that can assist a company’s management in decision making is Enterprise Resource Planning (ERP) system. It provides any information needed by the end users. So, this system can provide supports to all staffs in operation, managers in the middle level and top executives in the top level management. The information provided by this system can help the end users to do their functions within company properly. PT Ciliandra Perkasa as an agribusiness company needs information system support for its operational. This support will help company to get more competitive in oil palm agribusiness in Indonesia. This research implements quantitative method using primary data and secondary data sampling.